KEPERCAYAAN MASYARAKAT, PENGETAHUAN PERPAJAKAN, DAN TINGKAT EKONOMI TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI BANGUNAN DENGAN KONTROL PETUGAS KELURAHAN KABUPATEN SLEMAN SEBAGAI VARIABEL MODERATING - Ridhan Azka Hani Fanu, 15.05.62.0012; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2017)
This research was conducted with the aim to analyze public trust, knowledge of taxation, and economic level to taxpayer compliance in paying property tax with Sub Districts officer control as moderating variable.. The sample used in this study is the taxpayer building 2012-2015 in Sleman District. The method in sample selection in this study using sampling method. The number of samples in this study as many as 100 taxpayers in the district of Sleman. The hypothesis in this study was tested by using multiple linear regression analysis tools.The results showed that: The influence of Public Beliefs and Knowledge Taxation on taxpayer compliance in paying the has a significant positive effect, the influence of Economic Level on Taxpayer compliance in paying PBB in no significant effect. Sub Districts Officers' Control strengthens the Community's Trust on the Taxpayer Compliance in Sleman District. Sub Districts Officers Control does not strengthen Knowledge of Taxation and Economic Level to Taxpayer Compliance in Sleman City.Keywords: Public Trust, Knowledge of Taxation, and Economic Level